Handling Child Labor Problems in Indonesia: Post PROMOTE-ILO Project - Anggita Wulansari; Taufik Taufik; Alif Oktavian (Insignia: Journal of International Relations, 2023)
The practice of child labor is included in the form of violations of human rights so that it requires special attention and is handled seriously. The ILO as an international organization with a focus on child labor issues in the world certainly plays an important role in dealing with phenomena related to child labor, not only on a global scale but also on a national scale of its member countries, including Indonesia. This article aims to find out how the role of the ILO in dealing with the problem of child labor in Indonesia (2017-2021) uses Clive Archer's theory of the role of international organizations as an analytical tool. The method used is a qualitative method and is explained through descriptive analysis. The results of this study explain that in dealing with child labor in Indonesia, the ILO has acted as an instrument, an arena, and an actor. Through these three roles, the ILO has been able to carry out its role quite effectively so that the practice of child labor in Indonesia can be minimized. Keywords: child labor, Indonesia, International Labor Organization (ILO), the role of international organizations